IMMUNOLOGICAL RELATIONSHIP BETWEEN "LEPTOMONAS" pessoai (STRAIN PRINCIPS) C. fasciculata, L. brasiliensis AND T. cruzi BY THE AGAR GEL DIFFUSION TECHNIQUE PREVIOUS NOTE - Moreira de Souza, Maria do Carmo; Barbosa, William (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
The antigens of C. fasciculata, T. cruzi and L. brasiliensis showed crossreacting precipitin bands with the antigen of L. pessoai by the agar gel diffusion technique. T. cruzi formed two precipitin. bands, one of which showed reaction ipf identity with the antigen of. L. pessoai. C. fasciculata produced three precipitin bands, one of which showed immunological identity with the antigen of. L. pessoai. L. brasiliensis gave rise to a single band of precipitate which showed identity with the antigen of L. pessoai.